Plum (Prunus salicina) peel and pulp microparticles as natural antioxidant additives in breast chicken patties - Basanta, Maria Florencia; Rizzo, Sergio Anibal; Szerman, Natalia; Vaudagna, Sergio Ramon; Descalzo, Adriana Maria; Gerschenson, Lia Noemi; Perez, Carolina Daiana; Rojas, Ana María (2018)
Fiber microparticles (MPCs) separately obtained from peel and pulp of Japanese plum residues contained co-extracted β-carotene, lutein, and α- and γ-tocopherols, as well as polyphenols (cyanidins, quercetin derivatives, pentameric proanthocyanidins). Peel and pulp MPCs were then separately evaluated as natural antioxidant additives (2.0% w/w level) in raw breast chicken patty, susceptible to oxidation. Their effect on technological properties was also analyzed. MPCs reduced in 50% the formation of thiobarbituric acid reactive substances (TBARS) in raw patties during 10-days storage at 4.0 °C. Ferric reducing power (FRAP) was 77–157% higher in MPCs-added patties, especially with peel MPCs, being then attributed to the antioxidants supplied by these MPCs. It can be also associated to the highest α- and γ-tocopherol levels found in the peel MPCs-added patties, which remained high after cooking as well. Also, higher pectin and low lignin contents of pulp MPCs determined greater hydration, stabilized the cyanidins and, hence, the red color transferred to raw patties, and increased springiness of cooked patties. Plum peel and pulp MPCs are efficient additives for chicken meat products.